2001
DOI: 10.1210/jcem.86.5.7514
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-I Converting Enzyme Genotype-Dependent Benefit from Hormone Replacement Therapy in Isometric Muscle Strength and Bone Mineral Density1

Abstract: Low bone mineral density (BMD) and muscle weakness are major risk factors for postmenopausal osteoporotic fracture. Hormone replacement therapy (HRT) reverses the menopausal decline in maximum voluntary force of the adductor pollicis and reduces serum angiotensin-I converting enzyme (ACE) levels. The insertion (I) allele of the ACE gene polymorphism is associated with lower ACE activity and improved muscle efficiency in response to physical training. Therefore, we examined whether the presence of the I allele … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…This finding is supported by previous studies (28,29). The present study demonstrated that high bone turnover increased the RANKL/OPG ratio, followed by activation of the local bone RAS, which is supported by previous research (22).…”
Section: Discussionsupporting
confidence: 93%
“…This finding is supported by previous studies (28,29). The present study demonstrated that high bone turnover increased the RANKL/OPG ratio, followed by activation of the local bone RAS, which is supported by previous research (22).…”
Section: Discussionsupporting
confidence: 93%
“…In parallel and as expected, the grouping comparison and the correlation between age and Estradiol were statistically significant (rho = -0.773, p<0.001). These findings are consistent with previous research comparing pre-menopausal to post-menopausal [40], or post-menopausal Used_HRT vs No_HRT [15,16,48]. Our current, results are even more striking when one considers that in the HRT group, therapy had been ceased 10.6 ± 8.9 years prior to the current study and the levels of estrogen were now within expected post-menopausal levels [49,50].…”
Section: Estrogen Levels Affect Muscle Functionsupporting
confidence: 91%
“…In fact, work using amenorrheic [13] or post-menopausal females [14], is especially relevant here in demonstrating the theorem that estrogen is important for skeletal muscle structure and function. Indeed a substantial body of work shows a link between lowered circulating estrogen levels, and muscle atrophy as well as poor physical performance [15,16]. Also of note, is the previous research showing that obesity is one of the key factors linked to an overall increase in concentrations of free circulating biologically active estradiol (17β-estradiol).…”
Section: Introductionmentioning
confidence: 99%
“…A higher proportion of the DD genotype has been reported in elite sprint athletes when compared to endurance athletes and controls (Jones, Montgomery, & Woods, 2002;Myerson et al, 1999;Nazarov et al, 2001;Woods, D. et al, 2001). This genotype has been associated with a greater proportion of fast twitch fibres (Zhang et al, 2003), suggesting that this polymorphism may influence skeletal muscle function, although contradictory evidence also exists (Akhmetov et al, 2006).…”
Section: Introductionmentioning
confidence: 99%